Preparation method of low-density polyethylene grafted nano-montmorillonite modified PC / ABS (Polycarbonate / Acrylonitrile Butadiene Styrene)

Through the graft modification technology of LDPE-g-NMMT, the problem of insufficient thermal stability and flame retardancy of PC/ABS copolymers is solved, and the mechanical properties and flame retardant properties are significantly improved, providing better nanocomposites Material properties.

CN119286219APending Publication Date: 2025-01-10ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411489463.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

PC/ABS copolymers lack sufficient thermal stability, flame retardant and mechanical strength in some applications, and existing modifiers are difficult to effectively improve their performance.

Method used

Nanomontmorillonite (NMMT) is grafted by maleic anhydride (MAH) to form LDPE-g-NMMT as a compatibilizer or compatibilizer, and copolymerize with PC/ABS through melt blending technology. The material is combined to form a layered structure to improve compatibility and dispersion.

Benefits of technology

The mechanical properties, thermal stability and flame retardant properties of PC/ABS copolymers have been significantly improved. The introduction of LDPE-g-NMMT has improved the dispersion and mechanical strength of NMMT, making materials have a wider application prospect in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286219A_ABST
    Figure CN119286219A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of low-density polyethylene grafted nano-montmorillonite modified PC / ABS, and relates to the technical field of polymer composite material preparation, and the preparation method comprises the following steps: S1, pretreatment of NMMT; s2, preparation of the MAH grafted LDPE and the NMMT; s3, carrying out melt blending; s4, forming and processing; and S5, performance testing. According to the preparation method of the low-density polyethylene grafted nano-montmorillonite modified PC / ABS, the mechanical property, thermal stability and flame retardance of the PC / ABS copolymer can be remarkably improved, the thermal stability of the material is improved due to introduction of NMMT, and the flame retardance of the material is effectively improved due to the fact that a heat insulation barrier is formed in the combustion process due to the layered structure of NMMT. In addition, due to the introduction of LDPE-g-NMMT, the dispersity of NMMT is better, so that the mechanical strength of the material is remarkably enhanced, and the modified PC / ABS composite material has a wider application prospect in industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite material preparation, in particular to a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS. Background Art

[0002] PC and ABS copolymers are two widely used thermoplastics, both of which have excellent mechanical properties and processing properties. However, PC / ABS copolymers still need to further improve their thermal stability, flame retardancy and mechanical strength in some applications. NMMT, as a layered silicate, has high specific surface area, high thermal stability and good flame retardancy, and is an ideal modifier to improve the performance of PC / ABS.

[0003] Maleic anhydride (MAH) grafted NMMT is a method of grafting MAH onto the surface of NMMT through chemical reaction to improve the compatibility and dispersibility of NMMT with the polymer matrix. This modification can significantly improve the mechanical properties, thermal stability and processing properties of nanocomposites. For example, low-density polyethylene (LDPE) / MAH grafted LDPE / NMMT nanocomposites can be prepared by melt intercalation. The non-isothermal crystallization kinetics of the system can be studied by differential scanning calorimetry (DSC). The results show that the addition of NMMT and MAH grafted LDPE can significantly promote the crystallization of LDPE, increase the crystallization temperature and crystallization rate of LDPE, and play a role in heterogeneous nucleation. In addition, the effect of MAH grafted LDPE on LDPE / NMMT nanocomposites was studied. The addition of a suitable compatibilizer can significantly improve the interfacial compatibility between LDPE and NMMT, and significantly improve the mechanical properties of the composite. At the same time, the processing fluidity of the composite is also improved, and the fracture mode of LDPE changes from brittle fracture to ductile fracture. NMMT served as a carrier for peroxide in the melt grafting of MAH onto polypropylene. MAH was grafted onto PP in the presence of organically modified NMMT, where the concentration of MAH, peroxide concentration, and reaction time were varied. FTIR analysis showed that longer side chains were formed in the absence of NMMT. In the presence of NMMT, the concentration of MAH in the grafting reaction was not significant even at high DCP levels. These studies indicate that MAH grafting onto NMMT is an effective modification that can significantly improve the compatibility of the polymer matrix with NMMT and the properties of the composites. Nanocomposites with improved properties can be prepared through this modification.

[0004] The present invention is aimed at studying and improving the existing technology and its shortcomings, and provides a preparation method of low-density polyethylene grafted nano-montmorillonite modified PC / ABS. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS, comprising the following steps: S1. Pretreatment of NMMT: performing organic modification on NMMT to improve the compatibility of NMMT with the polymer matrix to obtain organic modified NMMT; S2, preparation of MAH-grafted LDPE and NMMT: the pretreated NMMT is mixed with MAH and LDPE in a ratio of 10:1:89 and stirred until the NMMT is evenly dispersed in the LDPE resin to improve the grafting efficiency, and then the mixture is melt-blended and extruded through a twin-screw extruder, and the composite modified masterbatch, i.e., LDPE-g-NMMT, is obtained after cutting; S3, melt blending: melt blending the mixed PC / ABS and LDPE-g-NMMT in a twin-screw extruder at a ratio of (95-80): (5-20); S4, molding processing: the melt-blended PC / ABS / LDPE-g-NMMT composite material is processed into a product of a desired shape by injection molding, extrusion or compression molding; S5. Performance test: The prepared PC / ABS / LDPE-g-NMMT composite material was subjected to performance test to verify the modification effect.

[0007] Furthermore, in step S1, the specific operation of the organic modification treatment is: mixing NMMT and a surfactant in a ratio of 95:5, mechanically stirring at 40-60° C. for a stirring time of ≥60 min, so that the surfactant molecules are inserted into the NMMT interlayer to form an organically modified NMMT.

[0008] Furthermore, in step S2, during the mixing and stirring process, auxiliary agents including initiators, antioxidants and solvents are added, the mixing temperature is controlled between 80 and 100° C., and the stirring time is ≥30 min.

[0009] Furthermore, in step S2, the extrusion temperature of the twin-screw extruder is 160-180° C., and the screw speed is 110-150 rpm.

[0010] Furthermore, in step S3, the screw extrusion temperature is 200-220° C., and the screw speed is 110-150 rpm.

[0011] Furthermore, in step S3, during the melt blending process, the speed and temperature of the extruder are adjusted to optimize the blending process to ensure that NMMT forms a good layered structure in the PC / ABS matrix.

[0012] Furthermore, in step S4, the specific operation of injection molding is: Mold preparation: Design and manufacture appropriate injection molds according to the shape and size requirements of the product. The precision and quality of the mold directly determine the appearance and performance of the final product; Material preparation: Dry the melt-blended PC / ABS / LDPE-g-NMMT composite material to ensure that the moisture content in the material meets the injection molding requirements; Injection molding process: Add the dried composite material into the hopper of the injection molding machine. The composite material is heated and melted in the barrel of the injection molding machine to form molten plastic. The molten plastic is pushed by the screw or plunger of the injection molding machine and injected into the mold cavity under high pressure. After the mold is closed, a certain pressure and temperature are maintained to cool and solidify the molten plastic in the mold. Open mold and take out the product: After the molten plastic is completely cooled and solidified, the injection molding machine opens the mold and takes the product out of the mold through the ejector or robot; Post-processing: Perform necessary finishing on the removed products, such as removing flash, gates, etc.

[0013] Furthermore, in step S4, the specific operation of extrusion molding is: Equipment preparation: Install the required die and auxiliary equipment (such as cooling water tank, tractor, etc.) for the extruder, and adjust the extruder parameters such as temperature, screw speed, and feeding speed; Material preparation: Dry the melt-blended PC / ABS / LDPE-g-NMMT composite material to ensure that the moisture content in the material meets the extrusion requirements; Extrusion process: The dried composite material is added into the hopper of the extruder. The composite material is heated and melted by the screw of the extruder and transported forward to the die. Then the molten plastic is extruded through the die into the desired shape (such as pipes, profiles, plates, etc.); Cooling and shaping: The extruded product is quickly cooled and shaped through a cooling water tank or air cooling device; Traction cutting: Use a traction machine to pull the cooled and shaped product to the cutting device for cutting to obtain the product of the required length.

[0014] Furthermore, in step S4, the specific operation of compression molding is: Mold preparation: Design and manufacture compression molds according to the shape and size requirements of the product, install the compression molds on the press, and perform preheating to ensure that the mold temperature meets the molding requirements; Material preparation: Pre-treat the melt-blended PC / ABS / LDPE-g-NMMT composite material (such as pre-pressing, pre-heating, etc.) to make it easier to form; Add materials and close the mold: add the pre-treated composite material into the mold and close the mold quickly; Pressure molding: Apply sufficient pressure to the mold through a press machine to gradually soften the composite material in the mold and fill the cavity. Maintain a certain pressure and temperature to cool and solidify the composite material in the mold; Demolding and taking out parts: After the composite material is completely cooled and solidified, open the mold, take the product out of the mold, and perform necessary trimming on the taken out product, such as removing flash and performing annealing treatment, etc., to improve the performance and quality of the product.

[0015] Furthermore, in step S5, the performance test specifically includes: 1) Mechanical properties test: used to measure the ability of materials to resist external forces without being damaged, including tests of tensile strength, impact strength, and bending strength indicators; Tensile strength test: Use a universal material testing machine to perform tensile tests on the composite materials in accordance with ASTM D638 or ISO 527 standards to measure the maximum force during the stretching process and its corresponding elongation at break; and compare it with unmodified PC / ABS materials to evaluate the effect of the addition of LDPE-g-NMMT on the tensile strength of the composite materials; Impact strength test: Use Izod impact tester or Charpy impact tester to test the impact strength of the composite material according to ASTM D256 or ISO180 standards to evaluate whether the modification of LDPE-g-NMMT improves the impact resistance of the composite material; Bending strength test: Use a three-point or four-point bending tester to test the flexural strength and modulus of the composite material in accordance with standards such as ASTM D790 or ISO 178, and analyze the effect of LDPE-g-NMMT modification on the flexural properties of the composite material; 2) Thermal stability test: used to evaluate the stability of materials in high temperature environments, including thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC); Thermogravimetric analysis (TGA): Using a thermogravimetric analyzer, the composite material is heated at a certain heating rate in a nitrogen or air atmosphere to measure the change in its mass with temperature, and to analyze the effect of the addition of LDPE-g-NMMT on thermal stability parameters such as the initial degradation temperature and the maximum thermal weight loss rate temperature of the composite material; Differential Scanning Calorimetry (DSC): Use a DSC instrument to measure the heat flow changes of the composite material during heating or cooling, evaluate its thermal performance parameters such as glass transition temperature (Tg) and melting temperature, compare the DSC curves of the composite material before and after modification, and analyze the effect of LDPE-g-NMMT on the thermal properties of the material; 3) Flame retardancy test: used to evaluate the flame retardancy of materials during combustion, including vertical burning test (UL94) and limiting oxygen index (LOI) test; Vertical combustion test (UL 94): According to the UL 94 standard, the composite material is made into a sample of a specified size, placed in a vertical combustion tester, ignited with a flame and its combustion behavior is observed. The flame retardancy of the composite material is evaluated based on the burning time of the sample, whether the dripping material ignites the absorbent cotton, and other standards; Limiting oxygen index (LOI) test: Use a limiting oxygen index meter to measure the oxygen concentration required for the composite material to maintain combustion under the lowest oxygen concentration in a mixture of nitrogen and oxygen; the higher the LOI value, the more difficult the material is to burn and the better the flame retardant performance; by comparing the LOI values ​​of the composite materials before and after modification, evaluate the effect of LDPE-g-NMMT on the flame retardant properties of the material.

[0016] The present invention provides a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS, which has the following beneficial effects: The invention provides a preparation method for modifying PC / ABS by grafting LDPE with MAH and NMMT, aiming to introduce NMMT, graft MAH with LDPE, form LDPE-g-NMMT as a compatibilizer or a compatibilizer, so as to improve the compatibility and dispersibility of PC / ABS and NMMT, thereby improving the mechanical properties, thermal stability and flame retardancy of the nano composite material.

[0017] The preparation method of the present invention can significantly improve the mechanical properties, thermal stability and flame retardancy of PC / ABS copolymers. The introduction of NMMT not only improves the thermal stability of the material, but also forms a heat insulation barrier during the combustion process due to its layered structure, effectively improving the flame retardancy of the material. In addition, the introduction of LDPE-g-NMMT makes the dispersibility of NMMT better, thereby significantly enhancing the mechanical strength of the material, so that the modified PC / ABS composite material has a wider application prospect in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The figure is a schematic flow chart of the steps of a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to the present invention; Figure 2It is a schematic diagram of performance test results of a preparation method of low-density polyethylene grafted nano-montmorillonite modified PC / ABS of the present invention. DETAILED DESCRIPTION

[0019] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0020] like Figure 1-Figure 2 As shown, a method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS comprises the following steps: S1. Pretreatment of NMMT: 95 g of NMMT was added with 5 g of surfactant and mechanically stirred at 50 °C for 1 hour; S2. Preparation of MAH-grafted LDPE and NMMT: 89 parts of LDPE, 10 parts of NMMT, 1 part of MAH, 0.1 parts of initiator (DCP), 0.1 parts of antioxidant (AT-10), and 0.5 parts of dimethylformamide (DMF) as solvent were melt-blended by twin-screw extrusion at a temperature of 160°C and a rotation speed of 110 rpm for 15 minutes to obtain LDPE-g-NMMT masterbatch; S3, melt blending: 100 g of the masterbatch was mixed with 900 g of PC / ABS resin, and melt blended in a twin-screw extruder at a temperature of 220° C. and a rotation speed of 140 rpm for 30 minutes; S4, molding processing: the melt-blended PC / ABS / LDPE-g-NMMT composite material is processed into a standard test sample by an injection molding machine; S5. Performance test: The prepared samples were subjected to thermogravimetric analysis (TGA), limiting oxygen index (LOI, which refers to the minimum oxygen concentration required for the material to maintain combustion in a nitrogen-oxygen mixture, i.e., volume percentage; the higher the LOI value, the more difficult the material is to burn and the better the flame retardant performance), tensile strength, elongation at break and notched impact strength tests to evaluate the performance of the material. The performance test results are as follows: Figure 2 As shown; In summary, the material prepared by this preparation method is significantly superior to the unmodified PC / ABS material in terms of mechanical properties, thermal stability and flame retardancy.

[0021] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.

Claims

1. A method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS, characterized in that: The following steps are involved: S1. Pretreatment of NMMT: performing organic modification on NMMT to improve the compatibility of NMMT with the polymer matrix to obtain organic modified NMMT; S2, preparation of MAH-grafted LDPE and NMMT: the pretreated NMMT is mixed with MAH and LDPE in a ratio of 10:1:89 and stirred until the NMMT is evenly dispersed in the LDPE resin, and then the mixture is melt-blended and extruded through a twin-screw extruder, and the composite modified masterbatch, i.e., LDPE-g-NMMT, is obtained after cutting; S3, melt blending: melt blending the mixed PC / ABS and LDPE-g-NMMT in a twin-screw extruder at a ratio of (95-80): (5-20); S4, molding processing: the melt-blended PC / ABS / LDPE-g-NMMT composite material is processed into a product of a desired shape by injection molding, extrusion or compression molding; S5. Performance test: The prepared PC / ABS / LDPE-g-NMMT composite material was subjected to performance test to verify the modification effect.

2. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In the step S1, the specific operation of the organic modification treatment is: NMMT and a surfactant are mixed in a ratio of 95:5, and mechanically stirred at 40-60° C. for a stirring time of ≥60 min, so that the surfactant molecules are inserted into the NMMT interlayer to form an organically modified NMMT.

3. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In the step S2, during the mixing and stirring process, auxiliary agents including initiators, antioxidants and solvents are added, the mixing temperature is controlled between 80 and 100° C., and the stirring time is ≥30 min.

4. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In the step S2, the extrusion temperature of the twin-screw extruder is 160-180°C, and the screw speed is 110-150 rpm.

5. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In the step S3, the screw extrusion temperature is 200-220° C., and the screw speed is 110-150 rpm.

6. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In the step S3, during the melt blending process, the speed and temperature of the extruder are adjusted to optimize the blending process and ensure that NMMT forms a layered structure in the PC / ABS matrix.

7. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In step S4, the specific operation of injection molding is: Mold preparation: design and manufacture suitable injection molds according to the shape and size requirements of the product; Material preparation: Dry the melt-blended PC / ABS / LDPE-g-NMMT composite material to ensure that the moisture content in the material meets the injection molding requirements; Injection molding process: Add the dried composite material into the hopper of the injection molding machine. The composite material is heated and melted in the barrel of the injection molding machine to form molten plastic. The molten plastic is pushed by the screw or plunger of the injection molding machine and injected into the mold cavity under high pressure. After the mold is closed, the pressure and temperature are maintained to cool and solidify the molten plastic in the mold. Open mold and take out the product: After the molten plastic is completely cooled and solidified, the injection molding machine opens the mold and takes the product out of the mold through the ejector or robot; Post-processing: Perform necessary trimming on the removed products.

8. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In step S4, the specific operation of extrusion molding is: Equipment preparation: Install the required die and auxiliary equipment for the extruder, and adjust the extruder parameters; Material preparation: Dry the melt-blended PC / ABS / LDPE-g-NMMT composite material to ensure that the moisture content in the material meets the extrusion requirements; Extrusion process: The dried composite material is added into the hopper of the extruder. The composite material is heated and melted by the screw of the extruder and transported forward to the die. Then the molten plastic is extruded into the desired shape through the die. Cooling and shaping: The extruded product is quickly cooled and shaped through a cooling water tank or air cooling device; Traction cutting: Use a traction machine to pull the cooled and shaped product to the cutting device for cutting to obtain the product of the required length.

9. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In step S4, the specific operation of compression molding is: Mold preparation: Design and manufacture compression molds according to the shape and size requirements of the product, install the compression molds on the press, and perform preheating; Material preparation: pre-treat the melt-blended PC / ABS / LDPE-g-NMMT composite material to make it easier to form; Add materials and close the mold: add the pre-treated composite material into the mold and close the mold quickly; Pressure molding: Apply sufficient pressure to the mold through a press machine to gradually soften the composite material in the mold and fill the cavity. Maintain the pressure and temperature to cool and solidify the composite material in the mold. Demolding and taking out the parts: After the composite material is completely cooled and solidified, open the mold, take the product out of the mold, and perform necessary trimming on the taken out product.

10. The method for preparing low-density polyethylene grafted nano-montmorillonite modified PC / ABS according to claim 1, characterized in that: In step S5, the performance test specifically includes: 1) Mechanical properties test: used to measure the ability of materials to resist external forces without being damaged, including tests of tensile strength, impact strength, and bending strength indicators; 2) Thermal stability test: used to evaluate the stability of materials in high temperature environments, including thermogravimetric analysis and differential scanning calorimetry; 3) Flame retardancy test: used to evaluate the flame retardancy of materials during combustion, including vertical burning test and limiting oxygen index test.